(3GdJagje dChGFd UfGYI GdJfLjes - (3eMeO Hf CMeO, CHh GdQjMGf GdHjQhfj GdNhGQRej,J (B440 (3g` s ((3Ydi Hf GdbGSe Hf CMeO Hf GdeLhd s)
(3ChdgG (B:s
(3hHYO , aEf GdEMGWI HgjFI GdYGde , hcjajI Tcd GdSeGA hGdCQV heG HjfgeG , Ydi hLg GdCNHGQ GdeCNhPI HGdJbdjO fGaYI LOkG s
(3BNQgG (B:s
(3hef JYOGgG abO YQV faSg hUfGYJg deG HdZJ Edjg , dCf ef GdSNQjI hGdESJgRGA , abO LgdgG GdefJSHhf EdjgG aVdkG Yf GdefJaYjf HgG hGddg GdeSJYGf, fLR HMeO Gddg s
(3HgG fXGe GdJYbjHIs
(3HgG LOGhd hCTcGds
(3fSNI KGfjIs
(3JJab ai ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa ai HYV GdCdaGX hGdYHGQGJ s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
Keywords: (3Gdadcs